Effect on distribution of siderite on aluminium – 7% silicon alloy by stir casting. (2020) - Krishnakumar, M.; Hariharan, J.; Saravanan, R.
Abstract: An investigation on distribution of Siderite (FeCO3 ) at the incremental at 1 Wt.% to Aluminium Matrix Composite (AMC) by stir casting. In preparing the Metal Matrix Composite (MMC), the FeCO3 was pre-heated at a temperatures of 200 °C and then added to the AMC. Microstructure of the MMC was observed using a metallurgical microscope. The distribution of FeCO3 on eutectic Si was revealed during the SEM imaging. Composition were analyzed using EDS. The result of the EDS analysis confirmed the presence of FeCO3 content on the MMC compared to the substrate. The elemental mapping shows the formation of intermetallic phase on the MMC. Further the compositions of intermetallic phases were obtained during the EDS analysis. The XRD spectrum confirms the presence of intermediate phases. The hardness and tensile strength of the MMC reinforced with FeCO3 at various wt% was found to be increased when compared to the MMC.